A spectral clustering-based optimal deployment method for scientific application in cloud computing. (4th May 2012) - Fan, Pei; Wang, Ji; Chen, Zhenbang; Zheng, Zibin; Lyu, Michael R.
Similar to Grid computing systems, scientific applications in cloud are large scale distributed systems that are deployed on distributed cloud nodes. Scientific applications usually have a lot of communications between the nodes for deployment. Therefore conventional ranking methods are not appropriate for deploying scientific applications. The reason is ranking methods do not consider the relations between nodes. We propose a novel spectral clustering based deployment method that takes not only the computing qualities of cloud nodes into account, but also the communication performance between different nodes. Experimental results show the effectiveness of our method for improving the performance of scientific applications.